Implementasi Metode Forward Chaining pada Aplikasi Cyber Counseling - Harahap, Febri Alfiani Putri; Damayanti, Fera; Lubis, Yessi Fitri Annisah; Khairunnisa, Khairunnisa; Syahputri, Nenna Irsa; Sundari, Siti (JiTEKH, 2024)
SMP Negeri 36 Medan has students with various backgrounds. Guidance and counseling is a support service provided by schools to students who have problems that can be resolved. The results of observations and interviews that have been conducted on counseling guidance teachers of SMP Negeri 36 Medan stated that they still find it difficult to deal with the problems faced by students. The method used in this study is the forward chaining method. The implementation of the forward chaining method in cyber counseling applications in overcoming problems that occur in students, aims to assist counseling guidance teachers and students in dealing with problems. The results of this study show that by using the forward chaining method in the cyber counseling application, the system can look for problems faced by counseling guidance teachers with students and the system can work according to the rules that have been set previously. Four counseling teachers conducted the system testing, which showed that 90% of the counseling teachers felt very helpful in knowing the problems of students through the cyber counseling application. In addition, testing also involved thirty students of SMP Negeri 36 Medan, where 95% of them were greatly helped by the cyber counseling application